Phytochemical screening, cytotoxicity, antimicrobial and anthelmintic activity of medical plants used in the treatment of lymphatic filariasis in the Eastern Cape, South Africa - Tiwani, Thumeka (University of the Free State, 2017)
Lymphatic filariasis is a disease caused by parasitic filarial nematodes that cause excessive swelling of the limbs, genitalia and breasts due to the distraction of the lymph system. This results in accumulation of lymph and lymphoedema. This disease is one of the neglected tropical diseases found in 38 African countries. In South Africa, there is no complete system for treatment of th is filarial disease. Many patients tend to opt for traditional help to alleviate the suffering caused by the disease. This research was aimed at identifying medicinal plants used as ethnomedicine for treating lymphatic filariasis and to assess the in vitro antimicrobia l, antifungal, antimycobacterial and anthelmintic activity of these medicinal plants. Six plant species (Platycarpha glomerata , Euphorbia gorgonis, Ricinus communis, Ledebouria sp., Rumex obtusifolius and Tulbaghia alliacea) were collected from Raymond Mhlaba and lntsika Yethu municipal areas of the Eastern Cape Province with the assistance of traditional healers and herbalists. Plant extracts were extracted with methanol, ethanol, water and acetone and screened for the presence of phytochemical components, antimicrobial, anthelminthic and cytotoxic properties. The organic solvent extracts of R. communis displayed good inhibitory properties against K. pneumoniae, S. aureus, E. coli and B. pumilus with MIC values ranging between 0.098 mg/ml and 1.56 mg/ml. All the extracts of P. g/omerata effective ly inhibited the growth of the bacterial strains with MIC values ranging from 0.098 to 1.56 mg/ml except the aqueous extract which displayed poor activity against K. pneumoniae with an MIC value of 12.5 mg/ml. All the extracts of T. al/iacea showed excellent inhibition of bacterial strains with MIC values ranging between 0.098 and 1.56 mg/ml. The best activity was also observed with the organ ic solvent extracts of E. gorgonis by inhibiting the bacterial growth at lowest concentrations of 0.098 and 0.195 mg/ml. The best antifungal inhibition against C. albicans was displayed by the organic solvent extracts of T. alliacea, R. obtusifolius, Ledebouria sp. and R. communis with MIC values ranging from 0.098 mg/ml to 1.56 mg/ml. with 50 % mortality while only the 0.5 mg/ml of T. alliacea and 1 mg/ml of P. glomerata acetone extracts exhibited good activity against S. equinus. This study has shown that medicinal plants assessed in this study have strong in vitro antibacterial, antifungal, anti-mycobacterial and anthelmintic efficacy which indicates that they are capable of acting against lymphatic filarial parasite infection. These observations are in agreement with indigenous knowledge provided by traditional healers. However, further in vivo studies using mammalian models are required in order to give conclusive evidence that these medicinal plant extracts can be used beyond reasonable doubt for treatment of lymphatic filariasis.
Keywords: Medicinal plant extracts; Antimicrobial; Cytotoxicity; Anthelmintic; Antimcycobacterial; Dissertation (M.Sc. (Plant Sciences))--University of the Free State, 2017; Lymphatic filariasis